The antibiotic ceftazidime is a singlet oxygen quencher as demonstrated by ultra-weak chemiluminescence and by inhibition of AAP consumption - Deby-Dupont, Ginette; Deby, Carol; Mouithys-Mickalad, Ange; Hoebeke, Maryse; Mathy-Hartert, Marianne; Jadoul, Luc; Vandenberghe, Alain; Lamy, Maurice (Biochimica et biophysica acta, 1998)
We demonstrated that the cephalosporin antibiotic ceftazidime (CAZ) deactivated singlet oxygen ( 1O 2). We then studied the mechanisms of the CAZ effects on the ultra weak chemiluminescence (uwCL) associated with the energy decay of 1O 2 generated by the Mallet reaction (H 2O 2+HOCl → HCl+H 2O+ 1O 2), and on the anthracene-9,10-dipropionic acid (AAP) consumption by 1O 2 generated by irradiation of Rose Bengal (RB). The uwCL generated by the Mallet reaction was amplified (6.2 times) by CAZ. The use of red and blue filters, which absorb radiation below 610 nm and between 470 and 700 nm respectively, demonstrated that CAZ increased the uwCL by a radiation emission at wavelengths shorter than the 633 and 704 nm wavelength emissions of 1O 2. CAZ was excited by scavenging the energy excess of 1O 2, which so returned to its fundamental state, while CAZ deactivated with light emission between 430–480 nm. CAZ also inhibited in a dose-dependent manner the consumption of AAP by 1O 2 generated by the irradiation of RB. The protection of AAP by 5×10 −3 M CAZ was equivalent to that of 10 −3 M histidine and 3×10 −6 M sodium azide. This process of 1O 2 deactivation will be useful in diseases characterized by an excessive PMN activation with a release of activated oxygen species.